Safety of endoscopic sphincterotomy in patients undergoing antithrombotic treatment: a retrospective study. (May 2019) - Yamamiya, Akira; Kitamura, Katsuya; Ishii, Yu; Mitsui, Yuta; Yoshida, Hitoshi
Background: This study investigated the safety of endoscopic sphincterotomy in patients undergoing antithrombotic treatment. Methods: From January 2014 to December 2016, a single-center retrospective study was conducted. Of the 80 patients with naïve papilla receiving antithrombotic treatment who underwent endoscopic sphincterotomy, 76 patients were retrospectively analyzed. We divided the participants into two groups as follows: 45 patients who discontinued antithrombotic treatment (discontinuation group) and 31 patients who continued antithrombotic treatment (continuation group). We evaluated the safety of endoscopic sphincterotomy in patients with naïve papilla who received antithrombotic treatment. Results: The percentage of patients requiring emergency endoscopic retrograde cholangiopancreatography in the continuation group was significantly higher than that in the discontinuation group (55% vs 11%; p = 0.001). The incidence of adverse events did not differ significantly between the two groups. Neither bleeding nor perforation occurred in either group. The length of hospital stay did not differ significantly between the two groups. Conclusions: Endoscopic sphincterotomy in patients undergoing antithrombotic treatment may be safe if the guidelines for gastroenterological endoscopy in patients undergoing antithrombotic treatment are followed.